Beneficios prevención y tratamiento de los antioxidantes en el cáncer oral. Scoping Review (2023)
Oral cancer is defined as an unlimited cellular alteration in the oral cavity, arising from several factors such as premalignant lesions, tobacco and alcohol, which play an important role. Antioxidants are molecules that are part of daily consumption foods and help prevent the adverse effects of reactive species